The 10 principles of food industry sustainability - Baldwin, Cheryl (Hoboken, NJ : Wiley Blackwell, 2015)
Although the food industry is beginning to make headway with itssustainability initiatives, substantially more progress is neededin order to feed the world's growing population sustainably. The challenge is that the topic of sustainability can seemoverwhelming and there is limited information that is specific tothe food industry. Written by an experienced food industry professional with yearsof experience in sustainability, The 10 Principles ofFood Industry Sustainability inspires and informs the progressrequired to nourish the population, revitalize natural resources, enhance economic development, and close resource loops. The bookmakes this complex topic approachable and actionable by identifyingthe most pressing sustainability priorities across the entire foodsupply chain and showing, with tools and examples, how producers, processors, packers, distributors, marketers and retailers all playa role in advancing improvement. The book begins with an overviewof the Principles of sustainability in the food industry: what theyare and why they matter. Subsequent chapters focus on each of theTen Principles in detail: how they relate to the food industry, their global relevance (including their environmental, health, andsocial impacts), and the best practices to achieve the potential ofmeaningful and positive progress that the Principles offer. Specific examples from industry are presented in order to providescalable solutions and bring the concepts to life, along with topresources for further exploration. The Principles, practices, and potential of sustainability inthe food industry covered in this book are designed to bemotivating and to offer a much-needed and clear way forward towardsa sustainable food supply.
Chapter 6 Distribution and Channels6.1 Transportation; 6.1.1 Refrigeration in transportation; 6.1.2 EPA SmartWay; 6.2 Facility management; 6.2.1 Refrigerants; 6.2.2 Cleaning and indoor environmental quality management; 6.2.3 Environmentally preferable purchasing; 6.2.4 Construction; 6.3 Gordon Food Service distribution and facilities improvements; 6.4 Food retailer J. Sainsbury addressing the environment; 6.5 Subway restaurants showing how to green operations; 6.6 Summary; Resources; References; Chapter 7 Food Waste; 7.1 The impacts from wastage; 7.2 Reducing wastage; 7.2.1 Waste management
Includes bibliographical references and index.
Keywords: Food industry and trade; Food supply; Sustainable agriculture; Farm produce; Animal products